The impact of the Great Recession on the Irish drug market - Windle, James (Criminology & criminal justice, 2018)
This article analyses 10 years (2004-2014) of An Garda Síochána controlled drug data to investigate the impact of economic recession and globalization on the Irish illicit drug market. The limited international literature on recessions and drug markets suggests that economic downturns can increase both drug consumption and dealing. Gardaí data may, however, suggest that the 2008 Great Recession reduced drug use and dealing, yet increased the cultivation and manufacture of drugs: trends which largely conflict with the international literature. Two testable hypotheses are drawn from the data: (1) net consumption and trade of illicit drugs were reduced by emigration triggered by the Great Recession; (2) the Great Recession forced an adaptation in the market which sped up the process towards import substitution of cannabis cultivation. The article concludes by investigating how recent changes highlight the globalized nature of Irish drug markets before proposing avenues for further research.